(untitled) (Journal of the College of Basic Education, 2025)
The research problem is to study the profound cultural and social influences on industrial jewelry designs, and how they develop in light of the rapid changes in tastes and fashion. The main objective of this study is to further understand how jewellery designers adapt and develop contemporary cultural and social transformations, as well as to identify the ways in which bold and new designs can capture the attention and interest of the target audience and how they can meet their diverse aspirations in the contemporary jewellery world. To achieve this goal, the study will include an in-depth analysis of the cultural and social factors that influence the design of jewellery and its various aspects, including cultural and contemporary customs and traditions, and socio-economic beliefs and values, and the changing interests and requirements of the target audience. In addition, the study will also include an analysis of the latest trends and fashions in the world of jewelry, and assess their impact on design trends and audience preferences. Using multiple research methodologies, this study will help to develop a deeper understanding of how cultural and social factors influence jewellery designs and trends, and provide valuable recommendations for designers and makers as well as those interested in the jewellery industry.